VOCABULARY LEARNING STRATEGIES (VLS) OF HIGH-ACHIEVING INDONESIAN EFL UNDERGRADUATE STUDENTS : A descriptive study carried out at one state university in Bandung - Vichet, Cham (2014)
Tujuanutamadaripenelitianiniadalahuntuk: 1). menyelidikistrategi-strategipembelajarkosa kata(VLS) yang seringdigunakanolehmahasiswa EFL Indonesia berprestasi di salahsatuuniversitasnegeridan 2). mengetahuialasanuntukpreferensi VLS mereka. Subyek yang dipilihdengansengajaadalah 55 siswa yang mengambiljurusanbahasaInggrisdanpendidikanbahasaInggris di departemenpendidikanbahasaInggrisdi salahsatuuniversitasnegeri di Bandung. Sebuahkuesioner 27-item, dengan alpha Cronbach (0,792) dan yang diadaptasidari (1997) taksonomi Schmitt untuk(VLSQ)bersamadenganpertanyaanterbukadigunakansebagaiinstrumenpenelitianutama. Hasilpenelitianmenunjukkanbahwarespondenadalahmenengahpenggunastrategistrategipembelajarankosakata (rata-rata = 2,8634). Selainitu, strategiyang paling seringdigunakanadalahstrategi Determinationdan Memory. Kata Kunci: Strategistrategipembelajarankosa kata The main purposes of this research are to: 1). investigate frequently used vocabulary learning strategies (VLS) by high-achieving Indonesian EFL undergraduate students at one state university and 2). find out the reasons for their preference of VLS. The purposively selected subjects were 55 students who majored in English language and English education at the department of English education of one state university in Bandung. A 27-item questionnaire, with Cronbach's alpha (.792) and which was adapted from Schmitt's (1997) taxonomy for VLSQ along with open questions was used as the main research instrument. The findings showed that the respondents were medium vocabulary learning strategies users (mean = 2.8634). In addition, Determination and Memory strategies were the most frequently used VLS. Key word: Vocabulary Learning Strategies (VLS)